17. KEJAHATAN TRANSNASIONAL DALAM PERSPEKTIF MARXISME : PENGARUH KULTUR EKSPLOITASI TERHADAP PENINGKATAN KASUS PERDAGANGAN MANUSIA DI MALAYSIA - Damara, Hilda Erika; Susiatiningsih, Hermini; Puspapertiwi, Sheiffi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
Human trafficking and forced labor has become most vital problem in the industrial world,especially in agriculture, such as agriculture, manufacture, construction and domestic work.Malaysia is well known as one of countries that has not succeed yet in controlling humantrafficking. In 2009 Malaysia has been classified on Tier3. Before 2007, Malaysia did nothave any law that specifically control human trafficking or people smuggling. However,Malaysia has made efforts to combat human trafficking cases in the previous year. UsingMarxism approach, this research tried to explain the reason behind increasing number ofhuman trafficking in Malaysia, in spite of existed regulations. The type of this research isexplanatory, using qualitative method. This research finds that there is exploitation cultureembedded in Malaysia’s social structure which causes high rate number of humantrafficking cases. Exploitation culture itself, as defined by Marxism, is attitute from masterto treat worker as an object, instead of human being.